Understanding Repurchase Intention of Online Marketplace Customers in Jakarta with Trust as Intervening - Siti Nurjanah; Agung Kresnamurti Rivai Prabumenang; Shandy Aditya (LPPM Universitas Negeri Jakarta, 2023)
The COVID-19 pandemic has a significant impact on the increased consumption and using digital services of Indonesian people. One of the digital services used is an e-commerce site. This phenomenon causes intense competition between e-commerce in Indonesia. The purpose of this study was to determine the significant effect of perceived usefulness and perceived ease of use on repurchase intention through trust. Data collection method by distributing online questionnaires through Google Forms. The sample in this study amounted to 252 respondents who live in DKI Jakarta, aged 18 – 38 years and have made purchases at online marketplace at least five times in the past year. Data analysis techniques used SPSS version 26 and SEM (Structural Equation Model) Lisrel version 8.8 to process data and analyze research data. The results showed that perceived usefulness has a significant effect on trust, perceived ease of use has a significant effect on trust, trust has a significant effect on repurchase intention, perceived usefulness has a significant effect on repurchase intention, perceived ease of use has a significant effect on repurchase intention, perceived usefulness has a significant effect on repurchase intention through trust, perceived ease of use has a significant effect on repurchase intention through trust.